Reduction in within-litter variation of piglet birth weight through dietary supplementation of 3-hydroxyisobutyric acid in sows - Che, Long; Niu, Lizhu; Liu, Le; Li, Mengyun; Huo, Wenying; Deng, Hongyu; Chen, Wen; Pang, Lifeng; Xu, Mengmeng (Frontiers in Veterinary Science, 2025)
Within-litter variations in birth weight (BW) influence piglet postnatal growth and survival rate. The present study investigated the effects of the valine metabolite 3-hydroxyisobutyric acid (3-HIB) on the birth weight of piglets by supplementing the sow diet with 3-HIB during late pregnancy. Forty sows were assigned randomly to the control (Con) group and 3-HIB supplementation groups (15 mg/kg body weight), with 20 sows per group. The experiment was conducted from day 85 of pregnancy until farrowing. 3-HIB supplementation significantly decreased the number of piglets with body weight < 1 kg, litter weight variation, and stillbirth number (p < 0.05) but had no significant effect on the organ index of newborn piglets. Compared to the control group, 3-HIB supplementation significantly increased the concentration of triglycerides in the placental tissue of sows (p < 0.05). The levels of total monounsaturated fatty acids and partial polyunsaturated fatty acids (C20:4 n-6, C20:5 n-3, and C22:6) in the plasma of piglets were significantly higher in the 3-HIB supplementation group than in the control group (p < 0.05). The results of lipid metabolism-related protein expression indicated that compared to the control group, the 3-HIB group significantly increased the expression of lipid transport-related proteins (solute carrier family 27a (SLC27A1) and fatty acid binding protein 3 [FABP3]) in the placenta of sows and fatty acid oxidation protein (carnitine palmitoyltransferase 1 [CPT-1]) in the muscle of piglets (p < 0.05). In conclusion, adding 3-HIB to the sow diet enhances piglet energy supply by promoting maternal-to-fetal fatty acid transport and fatty acid oxidation in piglet muscles, ultimately reducing within-litter body weight variation in newborn piglets.